Characterisation of tyre wear particle transport from road runoff to sea in coastal environments - Florence N.F. Parker-Jurd; Geoffrey D. Abbott; Daniel C. Conley; Cijo M. Xavier; Florian Pohl; Richard C. Thompson (Marine Pollution Bulletin, 2025)

A Non-destructive Method to Create a Time Series of Surface Area for Coral Using 3D Photogrammetry - Daniel D. Conley; Erin N. R. Hollander (Frontiers in Marine Science, 2021)
The wax dip method typically used to determine the surface area of corals for data normalization is destructive, rendering the collection of time series for such data impossible. With recent advancements in photogrammetric technology, it is now possible to collect these data in a non-destructive manner at very high levels of accuracy. This photogrammetric method using Agisoft’s Metashape is compared to the standard wax-dip method using both objects of known surface area and objects of unknown surface area. Objects of known surface area (i.e., objects that have surface areas that can be calculated using geometrical formulas) were estimated with a similar degree of accuracy with the Photogrammetry (PG) method ( R 2 = 0.9922, slope = 0.9835) as with the wax-dip method ( R 2 = 0.9872, slope = 1). A single factor ANOVA confirmed that there was no significant difference between measurements from the three methods of geometrical calculation, wax dipping, or photogrammetry for objects of known surface area. This paper describes the methods for rapidly collecting surface area data of small to moderately sized coral nubbins in a laboratory setting and characterizes the relationship between buoyant weight and surface area over time for the coral species Stylophora pistillata . Finally, two predictive models are proposed to estimate surface area from weight in air measurements.

Erratum to: Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giovanni Schifitto; et al. (Journal of NeuroVirology, 2011)

Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giavoni Schifitto; et al. (Journal of NeuroVirology, 2011)